Efficacy, safety, and predictors of response to infliximab therapy for ulcerative colitis - Mohamed G Fawaz; Khaled A.A Eid; Mohamed F Mohamed (Wolters Kluwer Medknow Publications, 2022)
Background Using infliximab (IFX), an antitumor necrosis factors antibody, has dramatically increased therapeutic choices for ulcerative colitis (UC). This study assessed IFX therapy's efficacy, safety, and action predictor variables for UC. Patients and methods This prospective interventional study was done on 50 patients with UC. Patients underwent colonoscopy, biopsy, complete blood count, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) before start of IFX and after 8 weeks. Patients started 5 mg/kg IFX infusion at 0, 2, and 6 weeks and then every eight weeks. After 6 months, cases were subjected to colonoscopy, biopsy, CRP, complete blood count, and ESR to assess IFX therapy. Results After therapy, hemoglobin and inactive UC cases (90%) increased significantly and white blood cell, ESR, and CRP decreased significantly than before treatment, without significant difference in platelet count. IFX treatment was associated with improvement in 90% of cases. There was a significant relation between improvement and colonoscopy, histopathology finding, and CRP after treatment (P<0.001) as the majority of cases had inactive UC, UC chronic phase with mild inflammation, and negative CRP after therapy. There was a nonsignificant relation between improvement and disease extension and severity (mayo clinic score) after the period. Conclusions Active UC cases treated by IFX had a better mucosal healing and clinical responses, corrected of anemia and thrombocytopenia and normalized acute-phase reaction.